Fiji : Disaster Risk Financing and Insurance - World Bank (Washington, DC, 2015)
This note aims to build understanding of the existing disaster risk financing and insurance (DRFI) tools in use in Fiji and to identify gaps where potential engagement could further develop financial resilience. In addition the note aims to encourage peer exchange of regional knowledge, specifically by encouraging dialogue on past experiences, lessons learned, optimal use of these financial tools, and the effect they may have on the execution of post-disaster funds. In 2012 alone Fiji experienced three major events with estimated total damage of F$146 million (US$78 million). Fiji is expected to incur, on average over the long term, annual losses of F$158 million (US$85 million) due to earthquakes and tropical cyclones. In the next 50 years Fiji has a 50 percent chance of experiencing a loss exceeding F$1,500 million (US$806 million). The country has a taken a proactive approach to DRFI and developed a finance manual for post-disaster budget execution. The government now has F$3 million (US$1.6 million) available in DRFI instruments to facilitate disaster response and also implemented tax concessions to encourage donations in the wake of tropical cyclone Evan. A number of options to support ongoing DRFI improvements in Fiji are presented for consideration: (a) the finance manual developed by the Ministry of Finance for post-disaster procedures should be finalized, and cabinet approval should be sought; (b) an overarching disaster risk financing and insurance strategy should be developed that includes options for risk transfer; and (c) assets should be identified in order to develop an insurance program for critical public assets.